2021
DOI: 10.15644/asc55/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Growth in Adolescence and its Influence on the Mandibular Incisor Crowding

Abstract: Background To analyze craniofacial growth during adolescence from the ages of 12 to 21 years and its relation to late mandibular incisor crowding. Material and Methods The study included 61 orthodontically untreated subjects (49% males). Lateral cephalograms were used to assess the jaw growth and inclination of the incisors. Little’s Irregularity Index and the anterior mandibular dental arch depth of mandibular dentition were measured. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several factors have been investigated in the search for the etiology of tooth crowding relapse, which happens after the end of active orthodontic treatment. Overall, it has been suggested that crowding in the lower anterior region and third molar impaction are both the sequela of inadequate growth [61][62][63]. In cases of restricted mandibular anterior growth and inefficient remodelling, enough space may not be generated for the mandibular incisors to move forward without getting crowded [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been investigated in the search for the etiology of tooth crowding relapse, which happens after the end of active orthodontic treatment. Overall, it has been suggested that crowding in the lower anterior region and third molar impaction are both the sequela of inadequate growth [61][62][63]. In cases of restricted mandibular anterior growth and inefficient remodelling, enough space may not be generated for the mandibular incisors to move forward without getting crowded [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The most pronounced growth is seen after the peak growth period of puberty [ 37 ]. The mandible grows particularly rapidly during this period, and this is most noticeable in cases of skeletal mandibular prognathism [ 40 ]. In particular, facial asymmetry is often associated with lateral mandibular deviation, which is an anteroposterior as well as a horizontal axial abnormality [ 1 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proffit groups adult patients into the categories of younger (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and older. As they achieve financial independence, adult patients seek the orthodontic treatment they wish they had growing up.…”
Section: Factors Allied To the Upsurge In Demandmentioning
confidence: 99%
“…18 In adolescent patients, more crowding of their anterior teeth happens because of maxillary and mandibular differential growth, with more misalignment occurring in the mandibular incisors. 19 In later age groups, this especially becomes an issue with the relative increase of lower teeth exposure on smiling. 20 As the problem presented in such cases results from teeth moving from their location, the rational solution would be to move them back to their original positions.…”
Section: Introductionmentioning
confidence: 99%